Enhancing knowledge of hypertension among general practitioners in Pakistan through a Train-The-Trainer initiative - Tariq Ashraf; Rafat Sultana; Musa Karim; Kanwal Fatima Aamir; Mustajab Mujtaba; Shoukat Memon; Deedar Hussain Gajju; Abdul Qadir Bhutto; Umair Arif; Hassan Irshad Bajwa; Naveed Shehzad; Haji Maqsood Mehmood; et al. (PLoS ONE, 2025)
Background Hypertension (HTN) affects over a billion people worldwide, with most cases in low- and middle-income countries (LMICs) where awareness and control remain low. In Pakistan, general practitioners (GPs) are usually the initial contact for hypertensive patients. Through the Train the Trainer (TTT) initiative, a group of consultant cardiologists were trained as master trainers to conduct training for GPs across Pakistan. This study aimed to assess the effectiveness of the TTT initiative regarding knowledge of GPs about the diagnosis and management of HTN. Methods This study included 540 GPs from all over Pakistan. Participants attended HTN training workshops run by Master Trainers under the TTT model and completed a structured online questionnaire in relation to knowledge of HTN before and 1–3 months after training. Knowledge scores were derived from correct responses for 19 items. Results Pre-training GPs demonstrated low HTN knowledge scores with a median of 26.3 [IQR: 15.8–36.8] and 92% scoring less than 50. In contrast, post-training medians increased significantly to 42.1 [IQR: 31.6–63.2], with 38.5% of GPs achieving moderate or high knowledge scores ≥50 (p < 0.001). Overall, gains were observed across all demographic groups; significant improvement was observed among female and younger GPs. Conclusions The TTT initiative effectively improved knowledge in both the diagnosis and management of hypertension among GPs, thus standing to potentially improve the current gaps in HTN care in many LMICs through similar models. Further studies are warranted to document the long-term clinical impact of this kind of training on patient outcomes and hypertension control.